Kontroversi Nikah Mut'ah - Mohammad Thoyyib Madani (KABILAH : Journal of Social Community, 2016)
Abstrak:Titik tolak perbedaan di kalangan fuqaha’ tentang nikah mut’ah bukan sekitar bolehnya nikah mut’ah, akan tetapi yang menjadi akar perdebatan dan perbedaan adalah apakah kebolehan nikah mut’ah itu terus berlaku sampai sekarang ataukah telah dibatalkan, sehingga diharamkan?. Masalah keberlakuan nikah mut’ah apakah masih atau tidak, pada dasarnya memang masalah ijtihadiyyah, tetapi kalangan sunniy telah sepakat bahwa nikah mut’ah diharamkan sampai hari kiamat. Sedang dikalangan Syi’ah, khususnya Syi’ah Imamiyyah, nikah mut’ah itu masih tetap berlaku sampai sekarang. Kata Kunci: Nikah mut’ah Abstract:The starting point of the differences among the jurists' about temporary marriages not around there is proper temporary marriages, but the root of the debate and the difference is whether the permissibility of temporary marriages were kept in force until now or has been canceled, so it is forbidden ?. Enforceability issue temporary marriages whether they or not, it's basically ijtihadiyyah problem, but the sunniy have agreed that temporary marriages forbidden until doomsday. Being among Shi'a, particularly Shi'a Imamiyyah, temporary marriages were still valid today. Keywords: Temporary marriages